School Interventions–based Prevention of Early‐Childhood Caries among 3–5‐year‐old children from very low socioeconomic status: Two‐year randomized trial - Samuel, Srinivasan Raj; Acharya, Shashidhar; Rao, Jeevika Chandrasekar (Journal of public health dentistry, 2020)
Objectives To assess the effectiveness of school‐based interventions to prevent early childhood caries (ECC) among preschool children from very low socioeconomic background over a period of 2 years. Materials and methods Four hundred and twenty preschool children between the ages of 3–5 years participated in this double blind, three parallel arm clinical trial. School only interventions such as prohibition of sugary snack consumption in school, teacher supervised daily brushing using fluoridated toothpaste, and oral health education were implemented with regular follow‐up at 6 months, 1, and 2 years. The study group had all three interventions, in active control‐tooth brushing and oral health education, and in negative control, only oral health education. Decay at d1/d2 using World Health Organization criteria, visible plaque and gingival inflammation were assessed at all follow‐ups. The value of P < 0.05 was considered significant. Results Absolute caries risk reduction in the study group was 20 percent and 12 percent when compared to active, negative controls after 2 years. Mean caries increment in the study group was 0.4 for d1/d2, for the active control group was 0.9 and negative control 0.8. The effect of interventions to prevent ECC in each group was calculated using the Çohen's d, and the study group had a score of 0.6 when compared with active controls and 0.9 in comparison to the negative control group. Conclusions Prohibition of sugary snacking in school and daily supervised tooth brushing, with or without oral health education is effective in preventing ECC among preschool children with health neglect in very low‐resource settings.